Resolving the phylogenetic position of Darwin's extinct ground sloth (Mylodon darwinii) using mitogenomic and nuclear exon data. Issue 1878 (16th May 2018) - Delsuc, Frédéric; Kuch, Melanie; Gibb, Gillian C.; Hughes, Jonathan; Szpak, Paul; Southon, John; Enk, Jacob; Duggan, Ana T.; Poinar, Hendrik N.
Abstract : Mylodon darwinii is the extinct giant ground sloth named after Charles Darwin, who first collected its remains in South America. We have successfully obtained a high-quality mitochondrial genome at 99-fold coverage using an Illumina shotgun sequencing of a 12 880-year-old bone fragment from Mylodon Cave in Chile. Low level of DNA damage showed that this sample was exceptionally well preserved for an ancient subfossil, probably the result of the dry and cold conditions prevailing within the cave. Accordingly, taxonomic assessment of our shotgun metagenomic data showed a very high percentage of endogenous DNA with 22% of the assembled metagenomic contigs assigned to Xenarthra. Additionally, we enriched over 15 kb of sequence data from seven nuclear exons, using target sequence capture designed against a wide xenarthran dataset. Phylogenetic and dating analyses of the mitogenomic dataset including all extant species of xenarthrans and the assembled nuclear supermatrix unambiguously place Mylodon darwinii as the sister-group of modern two-fingered sloths, from which it diverged around 22 million years ago. These congruent results from both the mitochondrial and nuclear data support the diphyly of the two modern sloth lineages, implying the convergent evolution of their unique suspensory behaviour as an adaption to arboreality. Our results offer promising perspectives for whole-genome sequencing of this emblematic extinct taxon.